2006
DOI: 10.1152/ajpheart.01343.2005
|View full text |Cite
|
Sign up to set email alerts
|

Selective spatiotemporal induction of matrix metalloproteinase-2 and matrix metalloproteinase-9 transcription after myocardial infarction

Abstract: Myocardial remodeling after myocardial infarction (MI) is associated with increased levels of the matrix metalloproteinases (MMPs). Levels of two MMP species, MMP-2 and MMP-9, are increased after MI, and transgenic deletion of these MMPs attenuates post-MI left ventricular (LV) remodeling. This study characterized the spatiotemporal patterns of gene promoter induction for MMP-2 and MMP-9 after MI. MI was induced in transgenic mice in which the MMP-2 or MMP-9 promoter sequence was fused to the beta-galactosidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 44 publications
5
93
0
3
Order By: Relevance
“…MMP-2 transcriptional activation occurred within the MI region, and persistent activation into the remote, viable myocardium could be observed by 1 mo post-MI. In this study, activation of the MMP-9 promoter was colocalized to inflammatory cells, whereas MMP-2 promoter activation was localized to cell types consistent with a fibroblast phenotype (286). These reporter studies clearly demonstrated that a robust and prolonged increase in MMP transcriptional activity occurs following MI and extends into the viable, normally perfused myocardium.…”
Section: Myocardial Restricted Overexpression/gene Transfer Studiessupporting
confidence: 52%
See 3 more Smart Citations
“…MMP-2 transcriptional activation occurred within the MI region, and persistent activation into the remote, viable myocardium could be observed by 1 mo post-MI. In this study, activation of the MMP-9 promoter was colocalized to inflammatory cells, whereas MMP-2 promoter activation was localized to cell types consistent with a fibroblast phenotype (286). These reporter studies clearly demonstrated that a robust and prolonged increase in MMP transcriptional activity occurs following MI and extends into the viable, normally perfused myocardium.…”
Section: Myocardial Restricted Overexpression/gene Transfer Studiessupporting
confidence: 52%
“…In other studies, the full-length promoter region for MMP-2 or MMP-9 fused to a reporter has been permanently ligated into the murine system (4,220,286). With the use of this approach, MMP transcriptional activity can be quantified as well as localized.…”
Section: Myocardial Restricted Overexpression/gene Transfer Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of different MMPs released from inflammatory cells and myofibroblast allow nascent scar formation. However, continuous and persistent release of MMPs beyond this initial healing process results in extracorporeal matrix instability, particularly in the infarct-viable border zone, and during remodelling of the extracellular matrix in remote healthy myocardium [16].…”
Section: The Role Of Mmps In the Pathophysiologymentioning
confidence: 99%